We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
60
1
avatar

http://prntscr.com/mt6dwm

 Mar 4, 2019
 #1
avatar+101856 
+1

y = -3x - 1

y = x^2 - 3x - 4

 

Set the y's equal

 

x^2 - 3x - 4 =  - 3x - 1        rearrange as

 

x^2 - 3 = 0

 

This has two solutions for x   = ±√3

 

cool cool cool

 Mar 4, 2019

9 Online Users